FIQH STUDY OF POWDERED BREAST MILK FROM THE PERSPECTIVE OF THE MALIKI AND SHAFI'I SCHOOLS IN THE NUSANTARA - Fathoni, M Insan; Awalia, Fadhila Tianti Mudi; Kamaluddin, Imam; Sa’adah, Yaumi (Universitas Islam Negeri Mataram, 2025)
This study explores the differing views of the Maliki and Shafi’i schools on whether breastfeeding using powdered breast milk (ASI Bubuk) establishes a mahram relationship. It also examines how this issue fits within Islam's social and cultural context in the Nusantara region. One of the key questions is whether transforming breast milk into powder changes its essential characteristics: color, taste, and smell. Using a comparative descriptive approach, this research highlights that both schools agree that powdered breast milk can create a mahram bond if its core properties remain unchanged, even when mixed with food, drinks, or medicine. However, they set different conditions. The Maliki school holds that a single feeding session is enough, whether the milk enters through the mouth or nose, as long as it reaches the stomach and provides nourishment. On the other hand, the Shafi'i school requires five separate breastfeeding sessions, all within the first two years of a child's life. Beyond the legal debate, this study also considers powdered breast milk's social and health implications in determining mahram relationships. Given the evolving ways breast milk is processed and used, further research involving other schools of thought could offer deeper insights into how Islamic law adapts to modern developments.